OUTILS DE MANAGEMENT DES ÉTABLISSEMENTS D’ENSEIGNEMENT SUPÉRIEUR PRIVÉ AU BÉNIN: DIAGNOSTIC ET PROPOSITION - HOUNKOU, Cossi Emmanuel; AKE, Natondé (My University, 2023)
Business management has mainly developed within private establishments, higher education financial literature. In addition, the uncertainty of the environment and the complex nature of the strategic decisions that organizational leaders must make often prevent them from relying on a logical process to decide. This is how private higher education establishments in Benin are regularly shaken by crises in terms of academic delays that are difficult to catch up on and which are not likely to help matters. This research attempts to identify the characteristics of the management of private higher education establishments in Benin
Keywords: Tools; Private Establishments; Management; Higher Education